Blocking effects in irreversible adsorption of linear macromolecules - Shelke, Pradip B.; Banpurkar, Arun G.; Ogale, S. B.; Limaye, A. V. (Surface Science, 2007)
{A new variant of random sequential adsorption (RSA), namely random sequential ballistic adsorption (RSBA), is proposed to explore the possible role of blocking effects in the adsorption dynamics of ballistically arriving objects. These objects upon adsorption can protrude outside the substrate and in turn can obstruct and hence reject the adsorption of newly arriving objects. Adsorption of linear macromolecules (modeled as infinitesimally thin needles), on a two-dimensional continuum substrate is studied using RSBA model. It is shown analytically that in late time regime, the number n(t) of adsorbed objects at time t follows a power law n(t) similar to t(alpha), as in RSA, but with a different exponent
Keywords: Adsorption; adsorption kinetics; Monte Carlo simulations; random sequential adsorption (RSA)

Impact of orientational distribution of adsorbing objects on dynamics of Random Sequential Ballistic Adsorption (RSBA) dynamics - Shelke, Pradip B.; Banpurkar, Arun G.; Ogale, Satishchandra B.; Limaye, A. V. (Surface Science, 2007)
Recently, by proposing a new variant of Random Sequential Adsorption (RSA) namely Random Sequential Ballistic Adsorption (RSBA) model [Pradip B. Shelke, A.G. Banpurkar, S.B. Ogale, A.V. Limaye, Surf. Sci. 601 (2007) 274], we addressed the issue of adsorption dynamics of extended objects where the objects, upon adsorption, protrude outside the substrate. This study brought out the role of the arriving trajectory in the adsorption dynamics. In the present work the possible role of the orientational distribution of the arriving objects in the RSBA dynamics is investigated. The dynamics of RSBA of needles (line segments) is studied analytically and by computer simulation for different types of theta distributions of arriving needles, theta being the angle made by the arriving needle with normal to the substrate. Three types of theta distributions, namely a uniform distribution over the range (0, pi/2), a Gaussian distribution and a distribution uniform over the solid angle, are considered. Analytical treatment establishes that in all the three cases, the number n(t) of adsorbed objects at a late time t follows a power law n(t) similar to t(alpha), and the exponent a depends on the specifics of the theta distribution. In general, for distribution f(theta) proportional to theta(beta), for theta -> 0, alpha is found to be 2/(beta + 3). The simulation results are in excellent agreement with the analytical findings and together they reveal that the orientational distribution of arriving objects has significant consequences for the Random Sequential Ballistic Adsorption (RSBA) process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Adsorption; adsorption kinetics; Monte Carlo simulations; random sequential adsorption (RSA)

Peculiarities of the adsorption kinetics of mixed convex plus concave contour objects - Shelke, Pradip B.; Ogale, S. B.; Khandkar, M. D.; Limaye, A. V. (Physical Review E, 2008)
Random sequential adsorption of mixed convex plus concave contour (MC) objects exhibits some distinctly different peculiar characteristics than the cases of purely convex objects. Though the substrate coverage approaches the jamming limit with time t as t(-p), same as that for convex objects, the law p similar to 1/d(f), valid for convex objects with d(f) degrees of freedom, does not hold for MC objects. Interestingly, for a fixed number of degrees of freedom, the exponent p changes with the degree of nonconvexity and bears a near perfect correlation with the same.